On Christmas eve : a Cape Light novel - Kinkade, Thomas, 1958-2012 (Kinkade, Thomas, 1958-2012. Cape Light novel, 2010)
In Cape Light a troubled marriage is healed by a runaway teenager and a divorced woman finds happiness with a struggling magazine writer who dresses up as Santa Claus.